Design sociology in theory and practice: An introduction (Sociologisk Forskning, 2026)
In recent years, design-oriented approaches have gained increasing attention within the social sciences and humanities. This article introduces and discusses design sociology, an interdisciplinary field that combines sociological theory with design methods. While the approach has been explored in international journals and books, there is a lack of Swedish literature addressing the topic. The purpose of this article is therefore to introduce design sociology and, through empirical examples, illustrate how it can be applied in practice. According to Professor Deborah Lupton, a leading scholar in the field, design sociology can be divided into three orientations: sociology of design, which analyses how design is influenced by social and cultural contexts; sociology through design, where design is used as a tool for sociological inquiry; and sociology with design, which involves collaboration between sociologists and designers or design researchers. Drawing on Lupton’s framework, the article discusses a previously conducted project in elderly care as an example of design sociology in practice. The article concludes with reflections on the opportunities and challenges of integrating design sociology into sociological research and higher education.
Keywords: design sociology; sociology; design methods; experiences; institutional ethnography